Vapor fluxes on the apical droplet during nanowire growth by molecular beam epitaxy [Phys. Status Solidi B 247(2), 254–258 (2010)]. Issue 8 (27th July 2015) - Glas, Frank
<x xml:space="preserve">Abstract</x> An error in Eq. (15) is corrected.